Sex and Tomato Flour Supplementation Influence Hepatic Function, Intestinal Morphometry, and Performance in Broilers - Arteaga, J.; Barreiro, G.; Concha, J.; Bulnes, C.; Reyna, S. (Faculty of Animal Science, IPB University, 2025)
Plant-derived supplements, such as tomato flour (TF), may enhance organ function and improve productive performance in poultry, but their effects under tropical conditions and between sexes remain unclear. This study assessed the effects of TF supplementation and sex on productive performance, hepatic function, and intestinal morphometry in broilers reared under tropical conditions. A total of 300 28-day-old Cobb-500 broilers were randomly allocated to six treatments: males and females fed a conventional diet or diets supplemented with 1% or 2% TF (T1-T6). Body weight, feed intake, and feed conversion ratio (FCR) were recorded weekly to evaluate productive performance. Intestinal morphometry (duodenum, jejunum, ileum), hepatic fatty infiltration (HFI), and liver function were analyzed. Supplementation with 1% TF improved final weight and FCR in male broilers (p<0.05). Supplementation with 2% TF reduced HFI in both sexes (p= 0.01) and lowered the albumin-to-globulin (A/G) ratio in males (p= 0.015). However, 2% TF impaired villus height and villus-to-crypt ratio in females, particularly in the duodenum and jejunum (p<0.05), while males were less affected. These findings indicate that TF enhances hepatic function and productive performance while reducing HFI in tropical-reared broilers. Its effects on intestinal morphometry are dose- and sex-dependent, with females being more negatively affected at higher doses, warranting further research into sex-specific dietary strategies.